Resilience factors in veterans of the Malvinas national war - Stein, Enrique (2016)
This article provides an overview of the factors of resilience in people who were part of the Malvinas war, indicating that the elements that favor the resilient community were collective self-esteem, cultural identity, social humor, spirituality , As well as within the negative ones we have to the governmental management, the fatalism and the Impunity. Also, some of the resilient factors mentioned by Saavedra (2005), developed in practice are identity, autonomy, satisfaction, pragmatism, links, networks, models, self-efficacy, learning and generativity.